Satellite Image West-Neuschwabenland 1:3 000 000 1981, Antarktis ... - Institut für Angewandte Geodäsie Now Bundesamt für Kartographie und Geodäsie, Frankfurt am Main (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie), Frankfurt am Main, 1982)
Satellite Image, NOAA-6-AVHRR, Record taken in Decembre 1981; Panoramically and affinely rectified, No map graticule, Coordinate marks at the map margins; Scale: 1:3000000;Projection: Polar Stereographic; Bounding Box: POLYGON ((-24 -68, 20 -68, 20 -74, -24 -79, -24 -68)) ...